Analisis kemampuan pemecahan masalah matematis siswa SMP pada materi peluang ditinjau berdasarkan gaya belajar - Rodiah, Siti Nur; Linda, Linda; Hidayat, Wahyu (IKIP Siliwangi, 2023)
The purpose of this research is to analyze and describe students' mathematical problem-solving abilities, especially in the matter of opportunities by using a scientific approach which is reviewed based on their learning style. The research subjects were 12 class VIII students. The method used in this research is descriptive qualitative. The instrument in this study was in the form of a written essay test on opportunity material with 6 questions with 5 indicators of mathematical problem-solving ability and interview guidelines. The result of this study shows that the mathematical problem solving ability of students with visual learning style obtained a percentage of 80% with the category